2013
DOI: 10.1007/s12262-013-0923-3
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Probiotic (Lactobacillus rhamnosus GG) and 5-ASA (Aminosalicylic Acid) in the Treatment of Experimental Radiation Proctitis in Rats

Abstract: The aims of the study are to demonstrate the effect of probiotic use on the healing of radiation proctitis (RP) and evaluate the efficiency of fecal biomarkers at follow-up of the treatment. Thirty-two male/female rats were randomly separated into four groups of eight rats. The first group (control) was not radiated. RP was created by 17.5 Gy single dose rectal irradiation. The second group (RP) was subjected to RP, but not treated. The third group (RP+ASA) was treated with 5-aminosalicylic acid (5-ASA) 250 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Non-invasive inflammatory biomarkers have been proposed to monitor the degree of radiation-induced gut-wall injury in the distal bowel and could be useful for the management of the disease. Among these, elastase [46] in mice, and lactoferrin in humans and in rats [47][48][49] were identified as markers. As a limitation, it has been reported that fecal elastase is strongly influenced by the surrounding environment [46].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive inflammatory biomarkers have been proposed to monitor the degree of radiation-induced gut-wall injury in the distal bowel and could be useful for the management of the disease. Among these, elastase [46] in mice, and lactoferrin in humans and in rats [47][48][49] were identified as markers. As a limitation, it has been reported that fecal elastase is strongly influenced by the surrounding environment [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, the administration of probiotics alone and probiotics plus honey resulted in bloating compared to the controls [82]. Studies on Lactobacillus and Bifidobacteria showed that administration after or before RT reduced the incidence of diarrhea and the use of antidiarrheal medication (loperamide) and resulted in a significant weight gain [83,100]. LGG was also found to be as effective as aminosalicylic acid (5-ASA), a standard treatment for proctitis, the inflammation of the rectum lining, in controlling the clinical and histopathological symptoms caused by radiation exposure in rat models [100,101].…”
Section: Probiotics Use As An Intervention To Radiation Toxicitymentioning
confidence: 99%
“…This problem may be due to differences in the bacterial strains used in the various studies. While a study on a probiotic combination containing B. longum, L. lactis, and E. faecium showed that probiotics could not help with weight gain post CRT, another survey of probiotics containing L. rhamnosus GG showed an increase in weight gain with probiotic administration post RT [100,102]. Furthermore, a systematic review on the effect of probiotics on GI symptoms induced by pelvic RT showed little evidence that probiotics can reduce diarrhea during or at the end of RT [105].…”
Section: Probiotics Use As An Intervention To Radiation Toxicitymentioning
confidence: 99%